The Integrasi Nilai Hukum Adat Badamai Masyarakat Banjar dalam Perancangan Peraturan Daerah Kalimantan Selatan sebagai Implementasi Keadilan Restoratif - Najwa Safira (CV Rewang Rencang, 2025)
Badamai customary law represents the Banjar community’s dispute resolution practice based on consensus and reconciliation. This study examines its legal position within Indonesia’s national law and the urgency of integrating its values into South Kalimantan Regional Regulations. The findings indicate that Badamai aligns with restorative justice principles and can strengthen local legal legitimacy. However, no specific regulation formally accommodates it. Therefore, a participatory integration strategy is required to ensure Badamai functions effectively within the regional legal system.